2012
DOI: 10.1055/s-0032-1304891
|View full text |Cite
|
Sign up to set email alerts
|

Fortschreibung der KoDiM-Studie: Kosten des Diabetes mellitus 2000–2009

Abstract: Cost of illness studies create transparency on the economic dimension of diseases. By now, the CoDiM study, based on administrative data of AOK Hesse und KV Hesse, identifies costs of people with diabetes and diabetes related excess costs in Germany for a period of 10 years. To date, additionally adjusted results are available by accounting for effects caused by inflation and ageing of the population. From 2000 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
26
0
7

Year Published

2013
2013
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(37 citation statements)
references
References 5 publications
4
26
0
7
Order By: Relevance
“…[7][8][9][10][11][12][13][14][15][16] For example, a study based on administrative health claims data (AOK/KV Hesse) showed that the excess direct medical costs of diabetes mellitus in 2009 averaged €21 billion in Germany. 17 Studies from the USA and England reported annual direct medical costs of $176 billion and £10 billion, respectively. 18 19 As one of the leading causes of morbidity and mortality, diabetes leads to a broad range of microvascular and macrovascular complications, such as retinopathy, nephropathy, neuropathy, stroke and myocardial infarction.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10][11][12][13][14][15][16] For example, a study based on administrative health claims data (AOK/KV Hesse) showed that the excess direct medical costs of diabetes mellitus in 2009 averaged €21 billion in Germany. 17 Studies from the USA and England reported annual direct medical costs of $176 billion and £10 billion, respectively. 18 19 As one of the leading causes of morbidity and mortality, diabetes leads to a broad range of microvascular and macrovascular complications, such as retinopathy, nephropathy, neuropathy, stroke and myocardial infarction.…”
Section: Introductionmentioning
confidence: 99%
“…Trotz des Wiissens um eine hohe, vermutlich in den letzten Jahrzehnten gestiegenen Prävalenz und Inzidenz in Deutschland überrascht, wie wenige Studien umfassende populationsbezogene und methodisch vertretbare Aussagen zur Prävalenz und Inzidenz von DM2 in Deutschland treffen. Verfügba-re Studien basieren entweder auf Angaben von Patienten [10,11,12,24], auf ausschließlich regionalen Daten gesetzlicher Krankenversicherungen (GKV) [8,9,13,14], Untersuchungen in einzelnen Bundesgebieten [17,19,21] oder nahezu 25 Jahre alten Daten aus der ehemaligen DDR [6]. Hinzu kommt, dass ein Großteil der Studien keine bzw.…”
unclassified
“…The disease may be acquired or inherited. High prevalence and incidence of type 2 diabetes make it an important disease (Koster et al, 2012). Prevalence of type 2 diabetes mellitus is raising worldwide (Gadsby, 2002;De Lusignan et al, 2005;Passa, 2002).…”
Section: Introductionmentioning
confidence: 99%